The Irrelevance of Environmental, Social, and Governance Disclosure to Retail Investors - Moss, Austin; Naughton, James P.; Wang, Clare (Management Science, 2024)
Using an hourly data set on retail investor individual security positions from Robinhood Markets, we find no evidence that environmental, social, and governance (ESG) disclosures inform retail investors’ buy and sell decisions. The response on ESG press release days by retail investors is indistinguishable from nonevent days. In contrast, these same investors make economically meaningful changes to their portfolios in response to non-ESG press releases, especially those that pertain to earnings announcements. We use stock return tests to show that there is economic content in ESG press releases, and we conduct subsample analyses showing that retail investors do not respond to the most salient and economically transparent ESG disclosures. Collectively, these tests suggest that a lack of economic content, a lack of visibility, and difficulty with investment integration are unlikely to explain our findings. This paper was accepted by Suraj Srinivasan, accounting. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2023.4822 .